Evaluasi Kebijakan Penanggulangan Banjir Di Kota Dumai Dalam Perspektif Kolaboratif Governance - Ahmad Arizul Samsen Limbong; Eko Priyo Purnomo; Tiara Khairunnisa (Journal of Governance Innovation, 2025)
Dumai City is still experiencing high-intensity flooding due to inadequate flood management. This flood had terrible consequences. In the short term, flooding can disrupt daily activities, reduce sales, and sometimes cause death. Floods can damage the environment and make obtaining clean water more difficult in the long term. This study was conducted using a qualitative methodology and descriptive approach. Several important parties involved in this research include the Dumai City Environmental Section, the Dumai City Tourism Section, and the Riau Natural Resources Conservation Center. The results show that people in Dumai City are working together to overcome flooding. they are limited, so each stakeholder has a task that can be done. All parties must agree to work together to overcome flooding in Dumai City. The institution's human resources do not know what main tasks and functions to carry out due to a change of position. Thus, stakeholders cannot obtain information quickly, which hampers the collaborative process to reduce flooding in Dumai City.